From ultra-depleted harzburgite to refertilized lherzolite: Multi-stage metasomatism and crustal recycling recorded by garnet populations from the Newlands Kimberlite, South Africa - C. Bonadiman; L. Milani; R. Tassinari; N. Lenhardt; P.W.J. Delport; L. Rowe (Lithos, 2026)

Managing and visualising geochemical data for tephra correlation with the IntChron Integration Tool - Victoria C. Smith; Danielle McLean; Eloise Wilkinson‐Rowe; Emma L. Horn; Gavin Kane; Christopher Bronk Ramsey (Journal of Quaternary Science, 2026)
There is now a wealth of glass‐shard geochemical data for volcanic ash (tephra) layers from a wide range of volcanoes and eruptions, providing invaluable datasets for tephrochronology. However, compilation of published data to assess tephra correlations leads to large files and requires careful management. Here, we show that a project within the IntChron Integration Tool (Ramsey et al., 2019), an open‐access and versatile online application, can be used to effectively store and manage tephra information, geochemical data and relevant metadata, while also providing visualisation and statistical tools. The visualisation functionality allows sites to be plotted on a variety of base maps, enables the plotting of tephra shard concentrations through a sequence and generates biplots of major and trace elements. The statistical tools are similarly invaluable for investigating compositional variability and relationships, and for assessing the probability that datasets correlate. An IntChron Integration Tool project supports the entire workflow, from sample and data collection through analysis and interpretation, to the generation of publication‐ready plots. Here, we present an example project to show the functionality using published data from distal tephra layers in the Lake Suigetsu core, and proximal eruption deposits from volcanoes across Japan. This project contains over 7000 geochemical analyses from 12 publications, demonstrating the power of the IntChron Integration Tool to manage, visualise and archive geochemical datasets.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Impact of diagenesis and acidic alteration on microbial fabrics and trace element distributions in fossilised siliceous hot spring deposits - Barbara J. Lyon; Michael C. Rowe; Andrew Langendam; Kathleen A. Campbell; Diego M. Guido; Ayrton R. Hamilton; Ema E. Nersezova; Amanda Galar; Dominique A. Stallard (Geochimica et Cosmochimica Acta, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Early intestinal barrier changes in A53T transgenic Parkinson’s disease mice - Myat Noe Han; Olivia Artaiz; Matthew C. Rowe; David I. Finkelstein; Shanti Diwakarla; Rachel M. McQuade (Cell and Tissue Research, 2026)
Gut dysfunction commonly precedes motor symptoms in Parkinson’s disease (PD), but the mechanistic sequence of gut versus brain pathology remains unclear. This work aimed to define the timing of intestinal barrier dysfunction relative to central nervous system (CNS) changes in the A53T α-synuclein transgenic mouse model of PD. Functional and molecular assessments of the gastrointestinal tract (ileum and colon) were conducted at 12 and 36 weeks. We measured in vivo and ex vivo intestinal permeability, nutrient absorption, histomorphology, goblet cell density, and expression of MUC2 and Claudin-1. Inflammatory markers (CRP, TNF-α, CD45) were quantified in plasma and gut tissues. A53T mice exhibited increased intestinal permeability at 12 and 36 weeks, with transiently elevated ex vivo transepithelial electrical resistance (TER) at 12 weeks. Nutrient absorption remained intact. Morphological changes included widened villi and crypts, altered mucin expression, and early reductions in Claudin-1 in the ileum and the colon while inflammatory markers remained largely unchanged. These findings suggest that gut dysfunction precedes known central pathology in A53T mice, supporting further investigation into the gut as an early site of pathology and a potential therapeutic target in PD.

Genomics Reveals Extensive Population Structure and Undescribed Phylogenetic Relationships in the Cascade Torrent Salamander ( Rhyacotriton cascadae ) - Christopher D. Cousins; Deanna H. Olson; Lindsay S. Millward; Michael J. Adams; Christopher A. Pearl; Jennifer C. Rowe; Tiffany S. Garcia (Journal of Biogeography, 2026)
Aim Aims of the study are to examine patterns of range‐wide genetic differentiation and population structure in a headwater obligate salamander living in a geologically rich region, to identify genetically distinct populations and areas of gene flow between them. Location Oregon and Washington in the Pacific Northwest, United States of America. Time Period Tissue samples were collected in 2022 and 2023. Major Taxa Studied The Cascade torrent salamander Rhyacotriton cascadae . Methods Utilisation of a genome‐wide single nucleotide polymorphism (SNP) dataset from across the species range to conduct a principal components analysis (PCA), Bayesian model of population structure, co‐ancestry matrix, phylogenetic tree and estimate genetic diversity. Results There are extensive levels of population structure within R. cascadae , including a previously unknown and highly differentiated clade. Structure is characterised by an island‐like pattern wherein the species is comprised of six populations that function as independent demographic units, with gene flow largely constrained within populations. Main Conclusions Our findings reveal cryptic population structure within R. cascadae , identifying six distinct populations across the range. The northernmost population in the northwest of the species range in Washington is surprisingly highly divergent from the other five populations, and the divergence was not previously known to science. While major rivers act as phylogeographic boundaries between some populations, these boundaries appear to not always be complete.

An initial map of European intertidal seagrass - Bede Ffinian Rowe Davies; Simon Oiry; Mar Roca; Philippe Rosa; Maria Laura Zoffoli; Dimitris Poursanidis; Tobias Dolch; Bárbara Ondiviela; Cristina Galván; Ana C. Brito; Richard J. Lilley; Laura L. Govers; et al. (Remote Sensing of Environment, 2026)

Different responses of Pinus sylvestris L. and Larix decidua Mill. to forest fire in Central England (UK) - Francesco Niccoli; Luigi Marfella; Jerzy P. Kabala; Jon Rowe; Rossana Marzaioli; Flora A. Rutigliano; Helen C. Glanville; Giovanna Battipaglia (Agricultural and Forest Meteorology, 2025)

Holocene hydroclimate inferred from alkane isotope and pollen records from monsoonal northern Australia - Michael I. Bird; Michael Brand; Rainy Comley; Xennephone Hadeen; Niels C. Munksgaard; Cassandra Rowe; Christopher M. Wurster; Costijn Zwart (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Accounting for the uncertainty in nitrogen deposition estimates in support of policy - Huw Woodward; Elizabeth Ramos Fonseca; Tim Oxley; Ed C. Rowe; Massimo Vieno; Eiko Nemitz; Helen ApSimon (Environmental Research, 2025)

Comparison of country-specific predictions of feed intake and methane emissions in sheep using different proxies - Q. Le Graverand; N. Lambe; F. McGovern; E.A. Navajas; P. Johnson; N. McHugh; I. De Barbieri; G. Ciappesoni; S. Rowe; B.A. Åby; J. Conington; C. Marie-Etancelin; et al. (Livestock Science, 2025)

El Zorro: early Jurassic intrusion-related gold (IRG) mineralization in the oldest, western-most segment of the Andean Cordillera of Northern Chile - Eduardo Fritis; Nicholas H. S. Oliver; Michael C. Rowe; Julie V. Rowland; Zeffron C. Reeves; Huiqing Huang (Mineralium Deposita, 2025)
The El Zorro gold district is the most recent gold discovery in the Coastal Cordillera of northern Chile. Ternera is the largest deposit in the district with total resources currently estimated at 1.282 Moz. New geology, geochemistry and geochronology data indicate that hydrothermal mineralization is mostly hosted within felsic to intermediate, ilmenite-bearing calc-alkaline dikes and stocks of the Upper Triassic to Lower Jurassic Relincho Pluton, and some of the adjacent Devonian to Carboniferous metasediments of the Chañaral Epimetamorphic Complex. Sheeted veins, veinlets, and fault zones with quartz, low amounts of pyrite, pyrrhotite and arsenopyrite, and local calcite are surrounded by narrow haloes of albite-biotite-quartz ± sulfides-K-feldspar-sericite-chlorite. Gold (mostly in the veins) is associated with elevated W-Bi and also As-Te-Sn, and not with iron enrichment or base metals, even though this system is proximal (~ 20 km) to IOCG and IOA deposits of the Coastal Cordillera. The main phase of gold mineralization occurred soon after emplacement of tonalitic dikes and granodiorite from the Relincho and Cuevitas plutons (U–Pb zircon between ~ 205 and 190 Ma), about 80 m.y. later than the development of orogenic fabrics. An absolute upper age limit is provided by compositionally distinct ore-cutting mafic dikes dated at 175–170 Ma (U–Pb apatite). The deposit falls into the intrusion-related gold category, as indicated by the cutting of earlier orogenic fabrics, the metal and alteration associations, and the spatial and temporal connection to reduced ilmenite-series intrusions, which are also very similar geochemically to the ‘type-locality’ IRG intrusions of the Tintina Belt in Yukon/Alaska. The El Zorro gold district represents the oldest and geologically western-most mineralizing event in the Central Andes of northern Chile, consistent with its time–space placement within the tectonic framework of easterly-younging mineralization and igneous activity in the Chilean Cordillera.

Systemic deficits in lipid homeostasis promote aging-associated impairments in B cell progenitor development - Silvia Vicenzi; Fangyuan Gao; Parker Côté; Joshua D. Hartman; Lara C. Avsharian; Ashni A. Vora; R. Grant Rowe; Hojun Li; Dorota Skowronska-Krawczyk; Leslie A. Crews (GeroScience, 2025)
Organismal aging has been associated with diverse metabolic and functional changes across tissues. Within the immune system, key features of physiological hematopoietic cell aging include increased fat deposition in the bone marrow, impaired hematopoietic stem and progenitor cell (HSPC) function, and a propensity towards myeloid differentiation. This shift in lineage bias can lead to pre-malignant bone marrow conditions such as clonal hematopoiesis of indeterminate potential (CHIP) or clonal cytopenias of undetermined significance (CCUS), frequently setting the stage for subsequent development of age-related cancers in myeloid or lymphoid lineages. Human aging has also been associated with diverse lipid alterations across tissues, such as decreased phospholipid membrane fluidity that arises as a result of increased saturated fatty acid (FA) accumulation and a decay in n-3 polyunsaturated fatty acid (PUFA) species by the age of 80 years, however the extent to which impaired FA metabolism contributes to hematopoietic aging is less clear. Here, comprehensive multi-omics analyses uncovered a role for a key PUFA biosynthesis gene, ELOVL2 , in mouse and human immune cell aging. Whole transcriptome RNA-sequencing studies and complementary flow cytometric analyses of bone marrow from aged Elovl2 mutant (enzyme-deficient) mice compared with age-matched controls revealed global downregulation in lymphoid cell markers and expression of genes involved specifically in B cell development. These studies unveiled CD79B, a vital molecular regulator of lymphoid progenitor development from the pro-B to pre-B cell stage, as a putative surface biomarker whose loss is associated with accelerated immune aging. The lipidome of mutant versus wild-type mice also displayed significant changes in the biophysical properties of cellular membranes. To investigate the relevance of these finding to human bone marrow aging, analyses of a single cell RNA-seq dataset of human HSPCs across the spectrum of human development and aging uncovered a rare subpopulation (< 7%) of CD34 + HSPCs that expresses ELOVL2 in healthy adult bone marrow. This HSPC subset, along with CD79B -expressing lymphoid-committed cells, were almost completely absent in CD34 + cells isolated from elderly bone marrow samples. Together, these findings uncover new roles for lipid metabolism enzymes in the molecular regulation of cellular aging and immune cell function in mouse and human hematopoiesis. In addition, because systemic loss of ELOVL2 enzymatic activity resulted in downregulation of B cell genes that are also associated with lymphoproliferative neoplasms, this study sheds light on an intriguing metabolic pathway that could be leveraged in future studies as a novel therapeutic modality to target blood cancers or other age-related conditions involving the B cell lineage.

Evaluation of Rock Burstability with Mechanical Property Testing and Microscopic Image Analysis - J. Malki; I. Vennes; C. D. Rowe; H. S. Mitri (Rock Mechanics and Rock Engineering, 2025)

A new approach for assessing the radioecological risk associated with the legacy discharge of oil derived natural radioactivity in the UK North Sea - F. Dal Molin; D. Hunt; A. Dewar; S. Lozach; C. Phillips; B. Thomas; L. Warford; J.E. Parker; J. Walker; M. Chocholek; D.M. Paterson; H. Woodward-Rowe; et al. (Marine Pollution Bulletin, 2025)

Mid-term (5 years) impacts of wildfire on soil chemical and biological properties in a UK peatland - Luigi Marfella; Mark A. Ashby; Georgia Hennessy; Jon Rowe; Rossana Marzaioli; Flora A. Rutigliano; Helen C. Glanville (Applied Soil Ecology, 2025)

Resolving Symbiodiniaceae Diversity Across Coral Microhabitats and Reef Niches - Wyatt C. Million; Christian R. Voolstra; Gabriela Perna; Giulia Puntin; Katherine Rowe; Maren Ziegler (Environmental Microbiology, 2025)
Dinoflagellates of the family Symbiodiniaceae are important symbionts of diverse marine animals and they also occupy different environmental niches on coral reefs. The link between diversity at ecosystem‐scale to microhabitats of Symbiodiniaceae within the coral holobiont is largely unknown. Using ITS2‐amplicon sequencing, we compared Symbiodiniaceae communities across four environments (seawater, near‐reef vs. distant sediments and turf algae) and two coral microhabitats (tissue, mucus) on a coral reef in the Red Sea. We found that coral and environmental habitats were both dominated by the genera Symbiodinium , Cladocopium and Durusdinium , but environmental habitats additionally harboured Fugacium , Gerakladium and Halluxium . Each environmental habitat harboured a distinct Symbiodiniaceae community. Nonetheless, 17 ITS2 sequences were shared among coral and environmental habitats and were also part of nearly half of the ITS2 type profiles in coral‐based communities. Tissues and mucus of 49 coral colonies from 17 genera had largely identical Symbiodiniaceae communities. Together with the large difference between environmental Symbiodiniaceae communities and those in the coral tissue and mucus, our results indicate a clear barrier between host‐associated and environmental Symbiodiniaceae communities marked by only few shared complete type profiles. Monitoring coral colonies after mucus sampling confirmed its suitability for long‐term monitoring of coral‐associated Symbiodiniaceae communities.

Taxonomic and environmental significance of Poaceae and Cyperaceae phytoliths from the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Woody plant phytolith morphology and representation in surface sediments across the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Intertidal seagrass extent from Sentinel-2 time-series show distinct trajectories in Western Europe - Bede Ffinian Rowe Davies; Simon Oiry; Philippe Rosa; Maria Laura Zoffoli; Ana I. Sousa; Oliver R. Thomas; Dan A. Smale; Melanie C. Austen; Lauren Biermann; Martin J. Attrill; Alejandro Roman; Gabriel Navarro; et al. (Remote Sensing of Environment, 2024)

Trace metal and organic biosignatures in digitate stromatolites from terrestrial siliceous hot spring deposits: Implications for the exploration of martian life - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Langendam; Cherie Tollemache; Barbara Lyon; Amanda Galar; Diego M. Guido; Bronwyn L. Teece; Trinity L. Hamilton (Chemical Geology, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

How background complexity impairs target detection - Zeke W. Rowe; Nicholas E. Scott-Samuel; Innes C. Cuthill (Animal Behaviour, 2024)

Okataina Volcanic Centre, New Zealand: Magmatic, volcanological, structural, thermal, and geothermal evolution of an active caldera system—Introduction - Cornel E.J. de Ronde; Ery C. Hughes; Yasuo Ogawa; Michael C. Rowe (Journal of Volcanology and Geothermal Research, 2024)

Speciation across biomes: Rapid diversification with reproductive isolation in the Australian delicate mice - Emily Roycroft; Fred Ford; Till Ramm; Rhiannon Schembri; William G. Breed; Phoebe A. Burns; Kevin C. Rowe; Craig Moritz (Molecular Ecology, 2024)
Phylogeographic studies of continental clades, especially when combined with palaeoclimate modelling, provide powerful insight into how environment drives speciation across climatic contexts. Australia, a continent characterized by disparate modern biomes and dynamic climate change, provides diverse opportunity to reconstruct the impact of past and present environments on diversification. Here, we use genomic‐scale data (1310 exons and whole mitogenomes from 111 samples) to investigate Pleistocene diversification, cryptic diversity, and secondary contact in the Australian delicate mice (Hydromyini: Pseudomys ), a recent radiation spanning almost all Australian environments. Across northern Australia, we find no evidence for introgression between cryptic lineages within Pseudomys delicatulus sensu lato, with palaeoclimate models supporting contraction and expansion of suitable habitat since the last glacial maximum. Despite multiple contact zones, we also find little evidence of introgression at a continental scale, with the exception of a potential hybrid zone in the mesic biome. In the arid zone, combined insights from genetic data and palaeomodels support a recent expansion in the arid specialist P. hermannsburgensis and contraction in the semi‐arid P. bolami . In the face of repeated secondary contact, differences in sperm morphology and chromosomal rearrangements are potential mechanisms that maintain species boundaries in these recently diverged species. Additionally, we describe the western delicate mouse as a new species and recommend taxonomic reinstatement of the eastern delicate mouse. Overall, we show that speciation in an evolutionarily young and widespread clade has been driven by environmental change, and potentially maintained by divergence in reproductive morphology and chromosome rearrangements.

Black-and-white pelage as visually protective coloration in colobus monkeys - Ossi Nokelainen; Sandra Winters; Zeke Rowe; Fernando A. Campos; Eva C. Wikberg; Natasha Howell; Tim Caro (Behavioral Ecology and Sociobiology, 2024)
Conspicuous coloration is often seen as the evolutionary consequence of either sexual selection or warning predators visually about prey defences, although not all conspicuous species fit this paradigm. Exceptions include several species of colobus monkeys whose black-and-white coloration, characteristic of larger colobines, has never been explained. Here, using photographs of black-and-white colobus ( Colobus vellerosus ) taken in the wild, quantitative image analysis, and vision modelling (acuity-corrected feline, chimpanzee, and raptor vision), we provide evidence that their coloration provides distance-dependent camouflage in natural forest environments. At all viewing distances, black-and-white colobus monkeys blend into their environment because of their high chromatic overlap with the background when viewed by ecologically relevant predator vision models which have low visual acuities. Additionally, for chimpanzee and felid vision, there was evidence of edge disruption at longer viewing distances. Our comparative analyses of different species of colobines do not support an association between black-and-white coloration and larger body mass or group size, but this may simply be due to the limited number of species within the family. We reason that black-and-white colobines gain visually protective coloration through background matching against felids, and also benefit through disruptive coloration against felids and chimpanzees but rely on these protective coloration mechanisms less against raptors. Significance statement Conspicuous black-and-white coloration in colobus monkeys has long eluded an evolutionary explanation. Our research, employing photographs of colobus monkeys, image analysis, and vision modelling, unveils a novel approach to this coloration. We show that in their natural forest habitats, black-and-white colobus monkeys employ distance-dependent camouflage against ecologically relevant predators with low visual acuity, blending in with the background at increasing viewing distances. In summary, the evolution of black-and-white colobus coloration appears to be related to background matching against felids, with added benefits of disruptive camouflage against felids and chimpanzees, less so to raptors, offering fresh insights into the complex interplay of coloration and survival strategies in mammals.

Exploring the internal textures and physical properties of digitate sinter in hot springs: Implications for remote sampling on Mars - Ema E. Nersezova; Michael C. Rowe; Kathleen A. Campbell; Andrew Ang; Steve Matthews; Steven W. Ruff; Ashok Meghwal; Ludmila Adam; Niamh Galligan; Thomas Loho (Planetary and Space Science, 2023)

Land degradation neutrality: Testing the indicator in a temperate agricultural landscape - Amy Thomas; Laura Bentley; Chris Feeney; Stephen Lofts; Ciaran Robb; Ed C Rowe; Amanda Thomson; Eleanor Warren-Thomas; Bridget Emmett (Journal of Environmental Management, 2023)

Guidelines for the selection of corrosion resistant alloys for CCS and CCUS injection wells - Bruce Craig; Adam Rowe; Michael Warmack; Thomas E. Doll; Catherine Stevens; Kevin C. Connors (International Journal of Greenhouse Gas Control, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

Population genomics of decline and local extinction in the endangered Australian Pookila - Phoebe A. Burns; Kevin C. Rowe; Marissa L. Parrott; Emily Roycroft (Biological Conservation, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Understanding caldera degassing from a detailed investigation at Lake Rotoiti, Okataina Volcanic Centre, New Zealand - Tsung-Han Jimmy Yang; Isabelle Chambefort; Agnes Mazot; Michael C. Rowe; Brad Scott; Nick Macdonald; Cynthia Werner; Tobias P. Fischer; Cornel E.J. de Ronde (Journal of Volcanology and Geothermal Research, 2023)

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Long-lived dacitic magmatic systems and recharge dynamics in the Jemez Mountains volcanic field, western USA - Jie Wu; Michael C. Rowe; Shane J. Cronin; John A. Wolff; Bin Fu (Contributions to Mineralogy and Petrology, 2022)
We examine the connected history of dacite-dominant volcanic rocks of the Tschicoma Formation, erupted between 5.5 and 2 Ma from the Jemez Mountains volcanic field, western USA. Zircon samples from two separate eruptions have continuous SHRIMP U–Pb age spectra spanning 0.84–1.08 Myr duration (3.12–3.96 Ma and 3.50–4.58 Ma, respectively), following an episode of zircon crystallization 0.28–0.50 Myr earlier (at 4.46 Ma and 4.86 Ma, respectively). Zircon chemical variations, as well as ubiquitous resorption textures that commonly show large core-rim age differences (up to 720–740 kyr), suggest that they grew in separate melt lenses. Zircons were likely stored at near-solidus or even sub-solidus conditions after crystallization, but may have been reactivated in response to at least four major magma recharge events every 300–400 kyr and smaller events in between. A cycle of zircon dissolution (from heating), recrystallization (during cooling), and storage repeated in different locations in the Tschicoma mush system throughout its lifespan; each recharge-induced heating stage may last for several hundred to more than a thousand years based on calculations of zircon dissolution. We envisage the melt lenses to be distributed in a crystal mush zone, coalescing into a single magma batch as magma recharge occurs shortly before eruption. Once active, increasing magma supply rates may trigger large-scale partial melting of the pre-existing mush and caldera-forming eruptions.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Trends of extreme air temperature and precipitation and their impact on corn and soybean yields in Nebraska, USA - Carlos A. C. dos Santos; Christopher M. U. Neale; Mesfin M. Mekonnen; Ivo Zution Gonçalves; Gabriel de Oliveira; Osias Ruiz-Alvarez; Babak Safa; Clinton M. Rowe (Theoretical and Applied Climatology, 2022)

Contrasting heat stress response patterns of coral holobionts across the Red Sea suggest distinct mechanisms of thermal tolerance - Christian R. Voolstra; Jacob J. Valenzuela; Serdar Turkarslan; Anny Cárdenas; Benjamin C. C. Hume; Gabriela Perna; Carol Buitrago‐López; Katherine Rowe; Monica V. Orellana; Nitin S. Baliga; Suman Paranjape; Guilhem Banc‐Prandi; et al. (Molecular Ecology, 2021)
Corals from the northern Red Sea, in particular the Gulf of Aqaba (GoA), have exceptionally high bleaching thresholds approaching >5℃ above their maximum monthly mean (MMM) temperatures. These elevated thresholds are thought to be due to historical selection, as corals passed through the warmer Southern Red Sea during recolonization from the Arabian Sea. To test this hypothesis, we determined thermal tolerance thresholds of GoA versus central Red Sea (CRS) Stylophora pistillata corals using multi‐temperature acute thermal stress assays to determine thermal thresholds. Relative thermal thresholds of GoA and CRS corals were indeed similar and exceptionally high (~7℃ above MMM). However, absolute thermal thresholds of CRS corals were on average 3℃ above those of GoA corals. To explore the molecular underpinnings, we determined gene expression and microbiome response of the coral holobiont. Transcriptomic responses differed markedly, with a strong response to the thermal stress in GoA corals and their symbiotic algae versus a remarkably muted response in CRS colonies. Concomitant to this, coral and algal genes showed temperature‐induced expression in GoA corals, while exhibiting fixed high expression (front‐loading) in CRS corals. Bacterial community composition of GoA corals changed dramatically under heat stress, whereas CRS corals displayed stable assemblages. We interpret the response of GoA corals as that of a resilient population approaching a tipping point in contrast to a pattern of consistently elevated thermal resistance in CRS corals that cannot further attune. Such response differences suggest distinct thermal tolerance mechanisms that may affect the response of coral populations to ocean warming.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Plant silicon application alters leaf alkaloid concentrations and impacts parasitoids more adversely than their aphid hosts - Casey R. Hall; Rhiannon C. Rowe; Meena Mikhael; Elizabeth Read; Sue E. Hartley; Scott N. Johnson (Oecologia, 2021)

Sperm Sizer: a program to semi-automate the measurement of sperm length - Callum S. McDiarmid; Roger Li; Ariel F. Kahrl; Melissah Rowe; Simon C. Griffith (Behavioral Ecology and Sociobiology, 2021)

Molecular and morphological systematics of the Bunomys division (Rodentia: Muridae), an endemic radiation on Sulawesi - Heru Handika; Anang S. Achmadi; Jacob A. Esselstyn; Kevin C. Rowe (Zoologica Scripta, 2021)
Sulawesi is the largest, most topographically complex island in the Wallacean biogeographic zone, and it has a rich fauna of endemic small mammals, dominated by rodents of the family Muridae. Among murids, the Bunomys division is the most species‐rich radiation on Sulawesi. In total, the division contains 11 genera and 32 species, five and 20 of which are endemic to Sulawesi. We combined a five‐locus phylogeny and linear cranial morphology to better understand the taxonomy and local scales of endemism within the Bunomys division on Sulawesi. Phylogenetic analyses of mitochondrial and nuclear DNA placed B. fratrorum among other genera and inferred Paruromys as sister to the type species of Taeromys ( T. celebensis ). We resolve these issues by resurrecting Frateromys , a genus under which B. fratrorum was once placed, and returning Paruromys dominator to Taeromys . Within three species, F. fratrorum, T. callitrichus, and T. taerae , we recovered Pleistocene age divergences between populations sampled across the northern peninsula of Sulawesi; divergence between western and eastern populations of F. fratrorum may reflect the existence of two species.

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Long-term decline in the parasitism rate of passionvine hopper eggs (Scolypopa australis) - D. P. Logan; C. A. Rowe; P. G. Connolly (BioControl, 2020)

Accounting for Carbon Flux to Mycorrhizal Fungi May Resolve Discrepancies in Forest Carbon Budgets - Andrew P. Ouimette; Scott V. Ollinger; Lucie C. Lepine; Ryan B. Stephens; Rebecca J. Rowe; Matthew A. Vadeboncoeur; Shersingh J. Tumber-Davila; Erik A. Hobbie (Ecosystems, 2020)

mGluR5 Allosteric Modulation Promotes Neurorecovery in a 6-OHDA-Toxicant Model of Parkinson’s Disease - Kyle Farmer; Khaled S. Abd-Elrahman; Alexa Derksen; Elyn M. Rowe; Ashley M. Thompson; Christopher A. Rudyk; Natalie A. Prowse; Zachary Dwyer; Samantha C. Bureau; Teresa Fortin; Stephen S.G. Ferguson; Shawn Hayley (Molecular Neurobiology, 2020)

Signaling from below: rodents select for deeper fruiting truffles with stronger volatile emissions - Ryan B. Stephens; Amy M. Trowbridge; Andrew P. Ouimette; W. Berk Knighton; Erik A. Hobbie; Paul C. Stoy; Rebecca J. Rowe (Ecology, 2020)
Many plant and fungal species use volatile organic compounds (VOCs) as chemical signals to convey information about the location or quality of their fruits or fruiting bodies to animal dispersers. Identifying the environmental factors and biotic interactions that shape fruit selection by animals is key to understanding the evolutionary processes that underpin chemical signaling. Using four Elaphomyces truffle species, we explored the role of fruiting depth, VOC emissions, and protein content in selection by five rodent species. We used stable isotope analysis of nitrogen (δ 15 N) in truffles to estimate fruiting depth, proton‐transfer‐reaction mass spectrometry to determine volatile emission composition, and nitrogen concentrations to calculate digestible protein of truffles. We coupled field surveys of truffle availability with truffle spore loads in rodent scat to determine selection by rodents. Despite presumably easier access to the shallow fruiting species, E. americanus (0.5‐cm depth) and E. verruculosus (2.5‐cm depth), most rodents selected for truffles fruiting deeper in the soil, E. macrosporus (4.1‐cm depth) and E. bartlettii (5.0‐cm depth). The deeper fruiting species had distinct VOC profiles and produced significantly higher quantities of odiferous compounds. Myodes gapperi (southern red‐backed vole), a fungal specialist, also selected for truffles with high levels of digestible protein, E. verruculosus and E. macrosporus . Our results highlight the importance of chemical signals in truffle selection by rodents and suggest that VOCs are under strong selective pressures relative to protein rewards. Strong chemical signals likely allow detection of truffles deep within the soil and reduce foraging effort by rodents. For rodents that depend on fungi as a major food source, protein content may also be important in selecting truffles.

Implications of different nitrogen input sources for potential production and carbon flux estimates in the coastal Gulf of Mexico (GOM) and Korean Peninsula coastal waters - Jongsun Kim; Piers Chapman; Gilbert Rowe; Steven F. DiMarco; Daniel C. O. Thornton (Ocean Science, 2020)
The coastal Gulf of Mexico (GOM) and coastal sea off the Korean Peninsula (CSK) both suffer from human-induced eutrophication. We used a nitrogen (N) mass balance model in two different regions with different nitrogen input sources to estimate organic carbon fluxes and predict future carbon fluxes under different model scenarios. The coastal GOM receives nitrogen predominantly from the Mississippi and Atchafalaya rivers and atmospheric nitrogen deposition is only a minor component in this region. In the CSK, groundwater and atmospheric nitrogen deposition are more important controlling factors. Our model includes the fluxes of nitrogen to the ocean from the atmosphere, groundwater and rivers, based on observational and literature data, and identifies three zones (brown, green and blue waters) in the coastal GOM and CSK with different productivity and carbon fluxes. Based on our model results, the potential primary production rate in the inner (brown water) zone are over 2 gC m−2 d−1 (GOM) and 1.5 gC m−2 d−1 (CSK). In the middle (green water) zone, potential production is from 0.1 to 2 (GOM) and 0.3 to 1.5 gC m−2 d−1 (CSK). In the offshore (blue water) zone, productivity is less than 0.1 (GOM) and 0.3 (CSK) gC m−2 d−1. Through our model scenario results, overall oxygen demand in the GOM will increase approximately 21 % if we fail to reduce riverine N input, likely increasing considerably the area affected by hypoxia. Comparing the results from the USA with those from the Korean Peninsula shows the importance of considering both riverine and atmospheric inputs of nitrogen. This has direct implications for investigating how changes in energy technologies can lead to changes in the production of various atmospheric contaminants that affect air quality, climate and the health of local populations.

Cereal aphid performance and feeding behaviour largely unaffected by silicon enrichment of host plants - Rhiannon C. Rowe; Piotr Trębicki; Andrew N. Gherlenda; Scott N. Johnson (Journal of Pest Science, 2020)

Reproductive coordination breeds success: the importance of the partnership in avian sperm biology - Laura L. Hurley; Melissah Rowe; Simon C. Griffith (Behavioral Ecology and Sociobiology, 2020)

Oceanic islands of Wallacea as a source for dispersal and diversification of murine rodents - Kevin C. Rowe; Anang S. Achmadi; Pierre‐Henri Fabre; John J. Schenk; Scott J. Steppan; Jacob A. Esselstyn (Journal of Biogeography, 2019)
Aim To determine the historical dynamics of colonization and whether the relative timing of colonization predicts diversification rate in the species‐rich, murine rodent communities of Indo‐Australia. Location Indo‐Australian Archipelago including the Sunda shelf of continental Asia, Sahul shelf of continental Australia, the Philippines and Wallacea of Indonesia. Taxon Order Rodentia, Family Muridae. Methods We used a fossil‐calibrated molecular phylogeny and Bayesian biogeographical modelling to infer the frequency and temporal sequence of biogeographical transitions among Sunda, Sahul, the Philippines and Wallacea. We estimated diversification rates for each colonizing lineage using a method‐of‐moments estimator of net diversification and Bayesian mixture model estimates of diversification rate shifts. Results We identified 17 biogeographical transitions, including nine originating from Sunda, seven originating from Sulawesi and broader Wallacea and one originating from Sahul. Wallacea was colonized eight times, the Phillipines five times, Sunda twice and Sahul twice. Net diversification rates ranged from 0.2 to 2.12 species/lineage/My with higher rates in secondary and later colonizers than primary colonizers. The highest rates were in the genus Rattus and their closest relatives, irrespective of colonization history. Main Conclusions Our inferences from murines demonstrate once again the substantial role of islands as sources of species diversity in terrestrial vertebrates of the IAA with most speciation events occurring on islands. Sulawesi and broader Wallacea have been a major source of colonists for both island and continental systems. Crossings of Wallace's Line were more common than subsequent transitions across Lydekker's Line to the east. While speciation following colonization of oceanic archipelagos and large islands is consistent with adaptive radiation theory and ideas regarding ecological opportunity, we did not observe a strong signal of incumbency effects. Rather, subsequent colonists of landmasses radiated unhindered by previous radiations.

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Liver and muscle glycogen oxidation and performance with dose variation of glucose–fructose ingestion during prolonged (3 h) exercise - Andy J. King; John P. O’Hara; Nicola C. Arjomandkhah; Josh Rowe; Douglas J. Morrison; Thomas Preston; Roderick F. G. J. King (European Journal of Applied Physiology, 2019)

Paleomagnetic determination of the age and properties of the 1780–1800 AD dome effusion/collapse episode of Mt. Taranaki, New Zealand - Geoffrey A. Lerner; Shane J. Cronin; Gillian M. Turner; Michael C. Rowe (Bulletin of Volcanology, 2019)

Gait stability in response to platform, belt, and sensory perturbations in young and older adults - S. Roeles; P. J. Rowe; S. M. Bruijn; C. R. Childs; G. D. Tarfali; F. Steenbrink; M. Pijnappels (Medical & Biological Engineering & Computing, 2018)

Isolation by marine barriers and climate explain areas of endemism in an island rodent - Thomas C. Giarla; Sean P. Maher; Anang S. Achmadi; Meagan K. Moore; Mark T. Swanson; Kevin C. Rowe; Jacob A. Esselstyn (Journal of Biogeography, 2018)
Aim The Indonesian island of Sulawesi is home to thousands of endemic terrestrial animal species. Phylogeographical studies of some of these taxa revealed concordant distribution patterns (areas of endemism; AoEs), suggestive of a shared evolutionary or ecological mechanism driving divergence among various terrestrial taxa. Generally, AoEs have been attributed to Pleistocene marine incursions, geological fault zones and Sulawesi's history as an archipelago. We test, for the first time, the hypothesis that population divergences are associated with unsuitable climate spaces at the boundaries between these areas. Location Sulawesi, Indonesia. Taxon Maxomys musschenbroekii , a common murid rodent endemic to Sulawesi. Methods We sequenced a mitochondrial gene, four nuclear protein‐coding genes and hundreds of ultraconserved elements from individuals sampled across the island, which we used to build intraspecific phylogenies and identify population structure. To test climate‐related hypotheses, we used multiple regression to assess the extent to which genetic distances, over‐land geographical distances, environmental distances (derived from ecological niche model resistance surfaces) and areas of endemism are correlated. Results In all three genetic datasets, we inferred phylogeographical structure that is geographically concordant with previously defined AoEs. Ecological niche models showed a similar geography of suitability across the island since the Last Glacial Maximum, with varying levels of unsuitable climate space between AoEs. Genetic distances were more strongly correlated with environmental distances than geographical distances and interspecific divergences arose just in the past 1.5 Myr. Main Conclusions Population divergences within M. musschenbroekii are consistent with AoE definitions from other taxa. Stable areas of unsuitable habitat near AoE boundaries probably supplemented marine incursions in generating population structure within M. musschenbroekii and other co‐distributed species.

Influence of porosity and groundmass crystallinity on dome rock strength: a case study from Mt. Taranaki, New Zealand - Edgar U. Zorn; Michael C. Rowe; Shane J. Cronin; Amy G. Ryan; Lori A. Kennedy; James K. Russell (Bulletin of Volcanology, 2018)

Incorporating linear programing and life cycle thinking into environmental sustainability decision-making: a case study on anchovy canning industry - I. Garcia-Herrero; J. Laso; M. Margallo; A. Bala; C. Gazulla; P. Fullana-i-Palmer; I. Vázquez-Rowe; A. Irabien; R. Aldaco (Clean Technologies and Environmental Policy, 2017)

The role of ecology, neutral processes and antagonistic coevolution in an apparent sexual arms race - Jennifer C. Perry; Colin J. Garroway; Locke Rowe (Ecology Letters, 2017)
Some of the strongest examples of a sexual ‘arms race’ come from observations of correlated evolution in sexually antagonistic traits among populations. However, it remains unclear whether these cases truly represent sexually antagonistic coevolution; alternatively, ecological or neutral processes might also drive correlated evolution. To investigate these alternatives, we evaluated the contributions of intersex genetic correlations, ecological context, neutral genetic divergence and sexual coevolution in the correlated evolution of antagonistic traits among populations of Gerris incognitus water striders. We could not detect intersex genetic correlations for these sexually antagonistic traits. Ecological variation was related to population variation in the key female antagonistic trait (spine length, a defence against males), as well as body size. Nevertheless, population covariation between sexually antagonistic traits remained substantial and significant even after accounting for all of these processes. Our results therefore provide strong evidence for a contemporary sexual arms race.

A geochemical approach to distinguishing competing tectono-magmatic processes preserved in small eruptive centres - Lucy E. McGee; Raimundo Brahm; Michael C. Rowe; Heather K. Handley; Eduardo Morgado; Luis E. Lara; Michael B. Turner; Nicolas Vinet; Miguel-Ángel Parada; Pedro Valdivia (Contributions to Mineralogy and Petrology, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

A Conceptualization of the Utility of Subjective Cognitive Decline in Clinical Trials of Preclinical Alzheimer’s Disease - Rachel F. Buckley; Victor L. Villemagne; Colin L. Masters; Kathryn A. Ellis; Christopher C. Rowe; Keith Johnson; Reisa Sperling; Rebecca Amariglio (Journal of Molecular Neuroscience, 2016)

Local endemism and within‐island diversification of shrews illustrate the importance of speciation in building Sundaland mammal diversity - Terrence C. Demos; Anang S. Achmadi; Thomas C. Giarla; Heru Handika; Maharadatunkamsi; Kevin C. Rowe; Jacob A. Esselstyn (Molecular Ecology, 2016)
Island systems are important models for evolutionary biology because they provide convenient, discrete biogeographic units of study. Continental islands with a history of intermittent dry land connections confound the discrete definitions of islands and have led zoologists to predict (i) little differentiation of terrestrial organisms among continental shelf islands and (ii) extinction, rather than speciation, to be the main cause of differences in community composition among islands. However, few continental island systems have been subjected to well‐sampled phylogeographic studies, leaving these biogeographic assumptions of connectivity largely untested. We analysed nine unlinked loci from shrews of the genus Crocidura from seven mountains and two lowland localities on the Sundaic continental shelf islands of Sumatra and Java. Coalescent species delimitation strongly supported all currently recognized Crocidura species from Sumatra (six species) and Java (five species), as well as one undescribed species endemic to each island. We find that nearly all species of Crocidura in the region are endemic to a single island and several of these have their closest relative(s) on the same island. Intra‐island genetic divergence among allopatric, conspecific populations is often substantial, perhaps indicating species‐level diversity remains underestimated. One recent (Pleistocene) speciation event generated two morphologically distinct, syntopic species on Java, further highlighting the prevalence of within‐island diversification. Our results suggest that both between‐ and within‐island speciation processes generated local endemism in Sundaland, supplementing the traditional view that the region's fauna is relictual and primarily governed by extinction.

Risk/Benefit Communication about Food—A Systematic Review of the Literature - L. J. Frewer; A. R. H. Fischer; M. Brennan; D. Bánáti; R. Lion; R. M. Meertens; G. Rowe; M. Siegrist; W. Verbeke; C. M. J. L. Vereijken (Critical Reviews in Food Science and Nutrition, 2016)

Empirical realised niche models for British coastal plant species - Susan G. Jarvis; Edwin C. Rowe; Peter A. Henrys; Simon M. Smart; Laurence Jones; Angus Garbutt (Journal of Coastal Conservation, 2016)

Magmatic–hydrothermal fluids and volatile metals in the Spirit Lake pluton and Margaret Cu–Mo porphyry system, SW Washington, USA - Alexander A. Iveson; James D. Webster; Michael C. Rowe; Owen K. Neill (Contributions to Mineralogy and Petrology, 2016)

Terrestrial runoff boosts phytoplankton in a Mediterranean coastal lagoon, but these effects do not propagate to higher trophic levels - A. Liess; O. Rowe; S. N. Francoeur; J. Guo; K. Lange; A. Schröder; B. Reichstein; R. Lefèbure; A. Deininger; P. Mathisen; C. L. Faithfull (Hydrobiologia, 2016)

Use of a robotic device to measure age-related decline in finger proprioception - Morgan L. Ingemanson; Justin B. Rowe; Vicky Chan; Eric T. Wolbrecht; Steven C. Cramer; David J. Reinkensmeyer (Experimental Brain Research, 2016)

Undetected Blooms in Prince William Sound: Using Multiple Techniques to Elucidate the Base of the Summer Food Web - Allison S. McInnes; Clifton C. Nunnally; Gilbert T. Rowe; Randall W. Davis; Antonietta Quigg (Estuaries and Coasts, 2015)

Groundmass crystallisation and cooling rates of lava-like ignimbrites: the Grey’s Landing ignimbrite, southern Idaho, USA - B. S. Ellis; B. Cordonnier; M. C. Rowe; D. Szymanowski; O. Bachmann; G. D. M. Andrews (Bulletin of Volcanology, 2015)

Terrestrial runoff may reduce microbenthic net community productivity by increasing turbidity: a Mediterranean coastal lagoon mesocosm experiment - A. Liess; C. Faithfull; B. Reichstein; O. Rowe; J. Guo; R. Pete; G. Thomsson; W. Uszko; S. N. Francoeur (Hydrobiologia, 2015)

Replenishment of volatile-rich mafic magma into a degassed chamber drives mixing and eruption of Tungurahua volcano - Madison L. Myers; Dennis J. Geist; Michael C. Rowe; Karen S. Harpp; Paul J. Wallace; Josef Dufek (Bulletin of Volcanology, 2014)

The benefit of offline sleep and wake for novel object recognition - Elizabeth A. McDevitt; Kelly M. Rowe; Mark Brady; Katherine A. Duggan; Sara C. Mednick (Experimental Brain Research, 2014)

A new synthesis of the molecular systematics and biogeography of honeyeaters (Passeriformes: Meliphagidae) highlights biogeographical and ecological complexity of a spectacular avian radiation - Leo Joseph; Alicia Toon; Árpád S. Nyári; N. Wayne Longmore; Karen M. C. Rowe; Tri Haryoko; John Trueman; Janet L. Gardner (Zoologica Scripta, 2014)
The passerine family Meliphagidae (the honeyeaters) comprises 175–180 species in 40–50 genera. It is an iconic element of the Australo‐Papuan avifauna and also occurs in Indonesia and on remote Pacific Ocean islands. Building on previous molecular studies that have pioneered a renewed understanding of the family's circumscription and systematics, we present an updated phylogenetic and systematics synthesis of honeyeaters derived from 112 mostly Australian, New Guinean and Wallacean species‐ and subspecies‐rank taxa aligned across 9246 positions spanning four mitochondrial and four nuclear genes. We affirm many of the recent changes advocated to the group's genus‐level systematics and offer some further refinements. The group's radiation appears to coincide broadly with the aridification of Australia in the Miocene, consistent with the time of origin of diversification of extant lineages in several other groups of Australian organisms. Most importantly, the complexity of the biogeography underlying the group's spectacular radiation, especially within Australia, is now apparent. Foremost among such examples is the robust evidence indicating that multiple, independent lineages of honeyeaters, including several monotypic genera, are endemic to the Australian arid zone, presumably having diverged and evolved within it. Also apparent and warranting further study are the phenotypic diversity among close relatives and the remarkably disjunct distributions within some clades, perhaps implying extinction of geographically intermediate lineages. Given such complexity, understanding the evolution of this radiation, which has thus far been intractable, relies on integration of molecular data with morphology, ecology and behaviour.

Impacts of Wetland Restoration Efforts on an Amphibian Assemblage in a Multi-invader Community - Jennifer C. Rowe; Tiffany S. Garcia (Wetlands, 2014)

Cryptic genetic diversity in Rattus of the San Francisco Bay region, California - Chris J. Conroy; Kevin C. Rowe; Karen M. C. Rowe; Pauline L. Kamath; Ken P. Aplin; Lucia Hui; David K. James; Craig Moritz; James L. Patton (Biological Invasions, 2013)

Plant traits and spread of the invasive salt marsh grass, Spartina alterniflora Loisel., in the Great Brak Estuary, South Africa - JB Adams; A Grobler; C Rowe; T Riddin; TG Bornman; DR Ayres (African Journal of Marine Science, 2012)

CCL20 Is Associated with Neurodegeneration Following Experimental Traumatic Brain Injury and Promotes Cellular Toxicity In Vitro - Christopher C. Leonardo; James Musso; Mahasweta Das; Derrick D. Rowe; Lisa A. Collier; Shyam Mohapatra; Keith R. Pennypacker (Translational Stroke Research, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

Quantification of total and particulate dimethylsulfoniopropionate (DMSP) in five Bermudian coral species across a depth gradient - D. M. Yost; R. Jones; C. L. Rowe; Carys Louise Mitchelmore (Coral Reefs, 2012)

Size increase in high elevation ground squirrels over the last century - Lindsey M. Eastman; Toni Lyn Morelli; Kevin C. Rowe; Chris J. Conroy; Craig Moritz (Global Change Biology, 2012)
There is increasing evidence for morphological change in response to recent environmental change, but how this relates to fluctuations in geographic range remains unclear. We measured museum specimens from two time periods (1902–1950 and 2000–2008) that vary significantly in climate to assess if and how two high elevation contracting species of ground squirrels in the Sierra Nevada of California, Belding's ground squirrel ( Urocitellus beldingi ) and the golden‐mantled ground squirrel ( Callospermophilus lateralis ), and one lower elevation, stable species, the California ground squirrel ( Otospermophilus beecheyi ), have responded morphologically to changes over the last century. We measured skull length (condylobasal length), an ontogenetically more labile trait highly correlated with body size, and maxillary toothrow length, a more developmentally constrained trait predictive of skull shape. C. lateralis and U. beldingi , both obligate hibernators, have increased in body size, but have not changed in shape. In contrast, O. beecheyi , which only hibernates in parts of its range, has shown no significant change in either morphometric trait. The increase in body size in the higher elevation species, hypothesized to be a plastic effect due to a longer growing season and thus prolonged food availability, opposes the expected direction of selection for decreased body size under chronic warming. Our study supports that population contraction is related to physiological rather than nutritional constraints.

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Stress-induced reinstatement of alcohol-seeking in rats is selectively suppressed by the neurokinin 1 (NK1) antagonist L822429 - Jesse R. Schank; Charles L. Pickens; Kelly E. Rowe; Kejun Cheng; Annika Thorsell; Kenner C. Rice; Yavin Shaham; Markus Heilig (Psychopharmacology, 2011)

Environmental change and declining resource availability for small‐mammal communities in the Great Basin - Rebecca J. Rowe; Rebecca C. Terry; Eric A. Rickart (Ecology, 2011)
Changes in climate and land use can impact natural systems across all levels of ecological organization. Most documented and anticipated effects consider species' properties, including phenologies, geographic distributions, and abundances. Responses of higher‐level aggregate community or ecosystem properties have not been considered as they are assumed to be relatively stable due to compensatory dynamics and diversity–stability relationships. However, this assumption may not be as fundamental as previously thought. Here we assess stability in the aggregate properties of total abundance, biomass, and energy consumption for small‐mammal communities in the Great Basin, using paired historical and modern survey data spanning nearly a century of environmental change. Results show marked declines in each aggregate property independent of spatial scale, elevation, or habitat type, and a reallocation of available biomass and energy favoring diet and habitat generalists. Because aggregate properties directly reflect resource availability, our findings indicate a regionwide decline in resources of ∼50% over the past century, which may signal a resource crisis. This work illustrates the power of using aggregate properties as indicators of ecological conditions and environmental change at broad spatial and temporal scales.

Compositional and thermal evolution of olivine-hosted melt inclusions in small-volume basaltic eruptions: a “simple” example from Dotsero Volcano, NW Colorado - M. C. Rowe; D. W. Peate; A. Newbrough (Contributions to Mineralogy and Petrology, 2011)

Amyloid Imaging in Alzheimer’s Disease and Other Dementias - Michelle T. Fodero-Tavoletti; Roberto Cappai; Catriona A. McLean; Kerryn E. Pike; Paul A. Adlard; Tiffany Cowie; Andrea R. Connor; Colin L. Masters; Christopher C. Rowe; Victor L. Villemagne (Brain Imaging and Behavior, 2009)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

A Genomewide Assessment of Inbreeding Depression: Gene Number, Function, and Mode of Action - JULIEN F. AYROLES; KIMBERLY A. HUGHES; KEVIN C. ROWE; MELISSA M. REEDY; SANDRA L. RODRIGUEZ‐ZAS; JENNY M. DRNEVICH; CARLA E. CÁCERES; KEN N. PAIGE (Conservation Biology, 2009)
Although the genetic basis of inbreeding depression is still being debated, most fitness effects are thought to be the result of increased homozygosity for recessive or partially recessive deleterious alleles rather than the loss of overdominant genes. It is unknown how many loci are associated with inbreeding depression, the genes or gene pathways involved, or their mode of action. To uncover genes associated with variation in fitness following inbreeding, we generated a set of inbred lines of Drosophila melanogaster for which only the third chromosome varied among lines and measured male competitive reproductive success among these lines to estimate inbreeding depression. Male competitive reproductive success for different lines validated our prediction that equally inbred lines show variation in inbreeding depression. To begin to assess the molecular basis of inbreeding depression for male competitive reproductive success, we detected variation in whole‐genome gene expression across these inbred lines with commercially available high‐density oligonucleotide microarrays. A total of 567 genes were differentially expressed among these inbred lines, indicating that inbreeding directly or indirectly affects a large number of genes: genes that are disproportionately involved in metabolism, stress and defense responses. Subsequently, we generated a set of outbred lines by crossing the highest inbreeding depression lines to each other and contrasted gene expression between parental inbred lines and F 1 hybrids with transcript abundance as a quantitative phenotype to determine the mode of action of the genes associated with inbreeding depression. Although our results indicated that approximately 75% of all genes involved in inbreeding depression were additive, partially additive, or dominant, about 25% of all genes expressed patterns of overdominance. These results should be viewed with caution given that they may be confounded by issues of statistical inference or associative overdominance.

Australian Rodents: Two Natural Experiments in Diversification of Murinae - Kevin C. Rowe (Journal of Mammalian Evolution, 2009)

Application of the probability-based Maryland Biological Stream Survey to the state’s assessment of water quality standards - Mark T. Southerland; Jon H. Vølstad; Edward D. Weber; Ronald J. Klauda; Charles A. Poukish; Matthew C. Rowe (Environmental Monitoring and Assessment, 2009)

Galantamine-induced improvements in cognitive function are not related to alterations in α4β2 nicotinic receptors in early Alzheimer’s disease as measured in vivo by 2-[18F]Fluoro-A-85380 PET - J. R. Ellis; P. J. Nathan; V. L. Villemagne; R. S. Mulligan; T. Saunder; K. Young; C. L. Smith; J. Welch; M. Woodward; K. A. Wesnes; G. Savage; C. C. Rowe (Psychopharmacology, 2009)

Abundance and demography of bottlenose dolphins in Dusky Sound, New Zealand, inferred from dorsal fin photographs - Rohan J. C. Currey; Lucy E. Rowe; Stephen M. Dawson; Elisabeth Slooten (New Zealand Journal of Marine and Freshwater Research, 2008)
The bottlenose dolphins ( Tursiops truncatus ) of Dusky Sound, Fiordland, New Zealand are a little‐studied group at the southern limit of the species range. Conducting a photo‐identification census and capture‐recapture analyses, we estimated there were 102 (CV = 0.9%) bottlenose dolphins in Dusky Sound during summer 2007/08, the first abundance estimate for this population. We did not encounter individuals from Doubtful Sound in Dusky Sound, suggesting little or no interchange between these neighbouring populations. Using a sex‐prediction model derived from laser‐metric photographs of dolphins in Doubtful Sound, we predicted the sexes of 79 individuals (98–99% of adults and sub‐adults) in Dusky Sound. Our predictions provided a sex ratio of 35 males to 44 females, not significantly different to a 1:1 ratio (G = 1.02, P > 0.05). High resighting rates of individual dolphins suggest the population may be resident, with dolphins observed throughout the entire fiord system.

Clonal dynamics in western North American aspen ( Populus tremuloides ) - K. E. MOCK; C. A. ROWE; M. B. HOOTEN; J. DEWOODY; V. D. HIPKINS (Molecular Ecology, 2008)
Clonality is a common phenomenon in plants, allowing genets to persist asexually for much longer periods of time than ramets. The relative frequency of sexual vs. asexual reproduction determines long‐term dominance and persistence of clonal plants at the landscape scale. One of the most familiar and valued clonal plants in North America is aspen ( Populus tremuloides ). Previous researchers have suggested that aspen in xeric landscapes of the intermountain west represent genets of great chronological age, maintained via clonal expansion in the near absence of sexual reproduction. We synthesized microsatellite data from 1371 ramets in two large sampling grids in Utah. We found a surprisingly large number of distinct genets, some covering large spatial areas, but most represented by only one to a few individual ramets at a sampling scale of 50 m. In general, multi‐ramet genets were spatially cohesive, although some genets appear to be fragmented remnants of much larger clones. We conclude that recent sexual reproduction in these landscapes is a stronger contributor to standing genetic variation at the population level than the accumulation of somatic mutations, and that even some of the spatially large clones may not be as ancient as previously supposed. Further, a striking majority of the largest genets in both study areas had three alleles at one or more loci, suggesting triploidy or aneuploidy. These genets tended to be spatially clustered but not closely related. Together, these findings substantially advance our understanding of clonal dynamics in western North American aspen, and set the stage for a broad range of future studies.

Evolution of biological dispersal corridors through a tectonically active mountain range in New Zealand - D. Craw; C. P. Burridge; P. Upton; D. L. Rowe; J. M. Waters (Journal of Biogeography, 2008)
Aim To assess the geological evolution and biogeographical implications of low mountain passes. In particular, we question the common biogeographical belief that major mountain belts form impervious physical barriers to biological dispersal, and that related taxa found on opposites sides of mountains are necessarily a result of vicariant tectonic processes. Location The Southern Alps of New Zealand form a long (500 km) narrow mountain belt at the oblique collisional Pacific–Australian tectonic plate boundary. High mountains were uplifted during the Pliocene (2–5 Ma) and uplift has continued to the present day. Methods We integrate previous work from several disciplines to obtain an overview of inter‐relationships between plate tectonic processes, geomorphology and biogeography along the main mountain barrier in New Zealand, and then extend this approach to other major mountain belts. Results The Southern Alps initially formed a barrier to at least some biological dispersal, including vicariant formation of separate species of freshwater non‐migratory galaxiid fish on either side. However, the high mountain barrier was breached in several places when passive transport of topography occurred, from the low‐erosion rain shadow on the eastern side towards the high‐erosion, high‐rainfall western side. This tectonic transport resulted in the capture of eastern rivers by west‐draining rivers, leaving low passes at the topographic divide. These low‐elevation corridors permitted biological dispersal across the mountains, although continued uplift raises these passes. A new set of passes has formed in the northern part of the mountains where younger faults are cutting across the older mountain topography. These potential dispersal corridors are becoming lower with continued erosion, and more common as the defining structures migrate southwards. Main conclusions Biological dispersal across the Southern Alps may be facilitated by numerous mountain passes, especially via the new passes formed by cross‐cutting faults. More low‐lying corridors existed than is readily apparent now, as old river capture‐related passes have been blocked by ongoing uplift. The dynamic mountain‐building and erosional environment typified by the Southern Alps occurs in all the world’s collisional mountain belts, such as the Andes, Himalayas, European Alps and North American Cordillera. Sister taxa occurring across mountain belts are not necessarily a result of vicariance driven by the rise of the mountains, as numerous passes may have permitted intermittent dispersal. The evolution of low passes may have been more prevalent than is currently appreciated, suggesting that topographically complex mountain ranges might be more effectively viewed as dynamic filters within a probability landscape rather than as static and impervious high‐altitude barriers to all but the rarest of biological dispersal events. In some cases, the biological disjunctions observed across mountains may more directly reflect habitat differentiation driven by orographic mountain development that has limited the probability of trans‐alpine dispersal success.

The ART of Loss: Aβ Imaging in the Evaluation of Alzheimer’s Disease and other Dementias - Victor L. Villemagne; Michelle T. Fodero-Tavoletti; Kerryn E. Pike; Roberto Cappai; Colin L. Masters; Christopher C. Rowe (Molecular Neurobiology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Social and ecological factors affecting paternity allocation in American robins with overlapping broods - Karen M. C. Rowe; Patrick J. Weatherhead (Behavioral Ecology and Sociobiology, 2007)

Defining population boundaries: use of three Bayesian approaches with microsatellite data from British natterjack toads ( Bufo calamita ) - G. ROWE; T. J. C. BEEBEE (Molecular Ecology, 2007)
Defining boundaries between populations is often difficult in the absence of information about current levels of gene flow. Such definitions can be important, however, both for the understanding of population dynamics and for conservation planning. Recently developed Bayesian methods for analysing genetic data now provide a powerful approach to this problem. Natterjack toads Bufo calamita are endangered in Britain, where their distribution is restricted to four geographically discrete regions. In three of these regions the boundaries between populations are often uncertain. We therefore used Bayesian approaches with microsatellite data to try and define British natterjack population structure, and thus inform conservation management. A large sample of natterjack toads from all 38 locations in Britain where the species is native was genotyped at eight microsatellite loci. The genetic diversity of natterjack populations declined as a function of increasing latitude, echoing postglacial colonization dynamics. Comparisons of three assignment methods ( structure , baps and geneland ) generated some broad similarities but also some inconsistencies in the definitions of population structure, especially in the most complex region (south Cumbria). Implications of the analyses for the future conservation of Bufo calamita in Britain are discussed.

Defining population boundaries: use of three Bayesian approaches with microsatellite data from British natterjack toads (Bufo calamita) - G. ROWE; T. J. C. BEEBEE (Molecular Ecology, 2007)

Vegetation Type Affects the Relationship Between Soil Carbon to Nitrogen Ratio and Nitrogen Leaching - E. C. Rowe; C. D. Evans; B. A. Emmett; B. Reynolds; R. C. Helliwell; M. C. Coull; C. J. Curtis (Water, Air, & Soil Pollution, 2006)

Comparative phylogeography of eastern chipmunks and white‐footed mice in relation to the individualistic nature of species - KEVIN C. ROWE; EDWARD J. HESKE; KEN N. PAIGE (Molecular Ecology, 2006)
Palaeoecological studies have demonstrated that ecological communities as a whole did not remain stable throughout the climatic fluctuations of the Quaternary. The result is that long‐term associations of species cannot be inferred by contemporary associations in ecological communities. Therefore, the evolutionary significance of any contemporary ecological interactions among species and of the biotic community within which species have evolved also cannot be assumed from contemporary conditions. Comparative phylogeographic data provide a method to identify species within ecological communities that have shared biogeographic histories. We present an example of a long‐term association between populations of two mammalian species, eastern chipmunks ( Tamias striatus ) and white‐footed mice ( Peromyscus leucopus ), which are commonly associated with deciduous forest habitats. The distribution of mitochondrial DNA variation in T. striatus and P. leucopus from previously glaciated regions of the eastern United States support the hypothesis that, in at least part of their range, genetic lineages of the two species have expanded from similar population sources since the Last Glacial Maximum. In addition, the spatial concordance of genetic lineages of T. striatus and P. leucopus with the oak‐savannah forest formations of Wisconsin and Illinois, suggest that populations associated with this community colonized the area in association with a set of arboreal species that comprise their deciduous forest habitat.

Neglected native or undesirable alien? Resolution of a conservation dilemma concerning the pool frog Rana lessonae - Trevor J. C. Beebee; John Buckley; Ivor Evans; Jim P. Foster; Antony H. Gent; Chris P. Gleed-Owen; Geoffrey Kelly; Graham Rowe; Charles Snell; Julia T. Wycherley; Inga Zeisset (Biodiversity and Conservation, 2005)

Nitrogen use efficiency of monoculture and hedgerow intercropping in the humid tropics - Edwin C. Rowe; Meine Van Noordwijk; Didik Suprayogo; Georg Cadisch (Plant and Soil, 2005)

Optimal mechanisms for finding and selecting mates: how threespine stickleback ( Gasterosteus aculeatus ) should encode male throat colors - M. P. Rowe; C. L. Baube; E. R. Loew; J. B. Phillips (Journal of Comparative Physiology A, 2004)

Seasonal profiles in growth, energy reserves, gonad development, and plasma steroids in age 1+ cultured Chinook salmon (Oncorhynchus tshawytscha) females - M. J. Unwin; C. W. Poortenaar; D. K. Rowe; N. C. Boustead; M. J. R. Porter (New Zealand Journal of Marine and Freshwater Research, 2004)
Sexual maturation in 2‐year‐old female Chinook salmon (Oncorhynchus tshawytscha) is unknown within their native range, but occurs in up to 20% of farmed stocks in New Zealand. To characterise the seasonal timing of oogenesis and subsequent ovarian development, we measured levels of plasma 17β‐estradiol and testosterone, condition factor, and gonadosomatic and hepatosomatic index, for freshwater‐reared female Chinook at 2–4‐week intervals during their second year of life (May 2001‐April 2002). These comprised two treatment groups under additional 24 h illumination from September to January, and two ambient controls. Macroscopic ovarian development first occurred in mid September (8 months before spawning), coinciding with detectable increases (≥0.3 ng ml ‐1 ) in both plasma steroids. Vitellogenesis was first observed in November and coincided with an increase in hepatosomatic index, possibly indicating the liver's role in transferring lipids to the developing ova. Neither mean weight nor the percentage of maturating fish (mean 6.9%) differed between the treatment and control groups at the end of the experiment, but ovarian development in the treatment group was advanced by 13 days relative to the controls. Reduced dark phase plasma melatonin levels confirmed that the additional light was sufficiently intense to produce a physiological response in the artificially illuminated fish.

Conserved simple sequence repeats for the Limnanthaceae (Brassicales) - V. K. Kishore; P. Velasco; D. K. Shintani; J. Rowe; C. Rosato; N. Adair; M. B. Slabaugh; S. J. Knapp (Theoretical and Applied Genetics, 2004)

Phylogenetic relationships of dengue-1 viruses from Argentina and Paraguay - G. Avilés; J. Rowe; J. Meissner; J. C. Manzur Caffarena; D. Enria; S. St. Jeor (Archives of Virology, 2002)

Nitrogen nutrition of hedged stock plants of Loblolly Pine. II. Influence of carbohydrate and nitrogen status on adventitious rooting of stem cuttings - D. Bradley Rowe; Frank A. Blazich; Barry Goldfarb; Farrell C. Wise (New Forests, 2002)

Nitrogen nutrition of hedged stock plants of Loblolly Pine. I. Tissue nitrogen concentrations and carbohydrate status - D. Bradley Rowe; Frank A. Blazich; C. David Raper (New Forests, 2002)

Implications of heterogeneity on procedures for estimating plant 15N recovery in hedgerow intercrop systems - E. C. Rowe; G. Cadisch (Agroforestry Systems, 2002)

Root distributions partially explain 15N uptake patterns in Gliricidia and Peltophorum hedgerow intercropping systems - Edwin C. Rowe; Meine van Noordwijk; Didik Suprayogo; Kurniatun Hairiah; Kenneth E. Giller; Georg Cadisch (Plant and Soil, 2001)

Accumulation and Selective Maternal Transfer of Contaminants in the Turtle Trachemys scripta Associated with Coal Ash Deposition - R. D. Nagle, C. L. Rowe, J. D. Congdon (Archives of Environmental Contamination and Toxicology, 2001)

Failed Recruitment of Southern Toads ( Bufo terrestris ) in a Trace Element-Contaminated Breeding Habitat: Direct and Indirect Effects That May Lead to a Local Population Sink - C. L. Rowe, W. A. Hopkins, V. R. Coffm (Archives of Environmental Contamination and Toxicology, 2001)

A brief view of known landmarks reorientates path integration in hamsters - A. S. Etienne; V. Boulens; R. Maurer; T. Rowe; C. Siegrist (The Science of Nature, 2000)

Recovery ofVerticillium dahliae from North American certified seed potatoes and characterization of strains by vegetative compatibility and aggressiveness - M. A. Omer; D. A. Johnson; R. C. Rowe (American Journal of Potato Research, 2000)

Considerations on the use of video playbacks as visual stimuli: the Lisbon workshop consensus - R. F. Oliveira; G. G. Rosenthal; I. Schlupp; P. K. McGregor; I. C. Cuthill; J. A. Endler; L. J. Fleishman; J. Zeil; E. Barata; F. Burford; D. Gonçalves; M. Haley; et al. (acta ethologica, 2000)

Polymerase chain reaction primers for microsatellite loci in the north European water frogs Rana ridibunda and R. lessonae - Inga Zeisset; Graham Rowe; Trevor J. C. Beebee (Molecular Ecology, 2000)

U-series dating of Hoxnian interglacial deposits at Marks Tey, Essex, England - P. J. Rowe; T. C. Atkinson; C. Turner (Journal of Quaternary Science, 1999)

U‐series dating of Hoxnian interglacial deposits at Marks Tey, Essex, England - P. J. Rowe; T. C. Atkinson; C. Turner (Journal of Quaternary Science, 1999)

Testing the safety-net role of hedgerow tree roots by 15N placement at different soil depths - E. C. Rowe; K. Hairiah; K. E. Giller; M. Van Noordwijk; G. Cadisch (Agroforestry Systems, 1998)

Elevated Trace Element Concentrations in Southern Toads, Bufo terrestris, Exposed to Coal Combustion Waste - W. A. Hopkins; M. T. Mendonça; C. L. Rowe; J. D. Congdon (Archives of Environmental Contamination and Toxicology, 1998)

Archive Contributions to a Molecular Phylogeography of the Toad Bufo calamita in Britain - T. J. C. Beebee; G. Rowe; T. Burke (Biochemical Genetics, 1998)

Phylogeography of the natterjack toad Bufo calamita in Britain: genetic differentiation of native and translocated populations - G. ROWE; T. J. C. BEEBEE; T. BURKE (Molecular Ecology, 1998)
The natterjack toad Bufo calamita is rare in Britain, which is at the northwestern edge of its biogeographical range. We investigated the level of genetic differentiation amongst almost all (34 out of 38) of the surviving British populations of this species, and among six new populations established by translocations during the 1980s. For eight microsatellite loci, allele sizes and frequencies were analysed using samples from each of these populations. The populations clustered into three robustly differentiated groups, each of which corresponded with a geographical region (east/southeast England, Merseyside and Cumbria). The Cumbrian populations showed a further weak geographical substructuring into northern and southern clades. The populations in south Cumbria were genetically more diverse than those in any of the other regions, as judged by the mean numbers of alleles per locus and the mean heterozygosity estimates. The translocated populations clustered close to their founders and, with one exception, did not differ significantly with respect to mean allele numbers, heterozygosity or polymorphism level. However, significant genetic differentiation (as measured by unbiased R ST ) was found between all but one of the founder‐translocation pairs. The implications of this phylogeographic study for the future conservation of B. calamita in Britain are discussed.

DQAsomes: A Novel Potential Drug and Gene Delivery System Made from Dequalinium™ - Volkmar Weissig; Jürgen Lasch; Gregory Erdos; Helmut W. Meyer; Thomas C. Rowe; Jeffrey Hughes (Pharmaceutical Research, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Resistance exercise training and the orthostatic response - John P. McCarthy; Marcas M. Bamman; Janice M. Yelle; Adrian D. LeBlanc; Roger M. Rowe; Michael C. Greenisen; Stuart M. C. Lee; Elisabeth R. Spector; Suzanne M. Fortney (European Journal of Applied Physiology, 1997)

Analysis of data captured by an on-line image capture system from an analytical ultracentrifuge using schlieren optics - A. C. Clewlow; N. Errington; A. J. Rowe (European Biophysics Journal, 1997)

PCR primers for polymorphic microsatellite loci in the anuran amphibian Bufo calamita - G. Rowe; T. J. C. Beebee; T. Burke (Molecular Ecology, 1997)

Influence of cultivar resistance toVerticillium SPP. On potato early dying - T. A. Wheeler; R. C. Rowe; R. M. Riedel; L. V. Madden (American Journal of Potato Research, 1994)

Future challenges in managing potato health - Randall C. Rowe (American Journal of Potato Research, 1992)

Seasonal variation and effects of wheat rotation on populations ofVerticillium dahliae Kleb. in Ohio potato field soils - T. R. Joaquim; V. L. Smith; R. C. Rowe (American Journal of Potato Research, 1988)

Lesion nematode involvement in potato early dying disease - Richard M. Riedel; Randall C. Rowe (American Journal of Potato Research, 1985)

Potato early dying—A serious threat to the potato industry - Randall C. Rowe (American Journal of Potato Research, 1985)

Preface - Randall C. Rowe (American Journal of Potato Research, 1985)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Relationship of foliar ozone injury to maturity classification and yield of potatoes - A. R. Mosley; R. C. Rowe; T. C. Weidensaul (American Journal of Potato Research, 1978)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Editorial - E. Norrby; W. P. Rowe; C. Scholtissek; D. A. J. Tyrrell; J. Vilček (Archives of Virology, 1975)

K. F. Meyer - S. Gard; C. Hallauer; A. Mayr; W. P. Rowe; J. Vilček (Archives of Virology, 1974)

A root inoculation technique to screen potato seedlings for resistance toPseudomonas solanacearum - Luis C. Gonzalez; Luis Sequeira; P. R. Rowe (American Journal of Potato Research, 1973)

Rat coronavirus (RCV): A prevalent, naturally occurring pneumotropic virus of rats - J. C. Parker; S. S. Cross; W. P. Rowe (Archives of Virology, 1970)